Assess Relationship between Nursing Practice Environment and Nurses’ Psychological Empowerment - Naifz Ali Alanazi,; Awad Waselallah Safar Al Thubaiti,; Abdullah Musleh Ayed Al Harithi,; Abdullah Faihan Naif Alotaibi,; Rashed Hazaa Hassen Althuwaybi,; Badr Awad Alaotaibi,; Saleh Saad Twaile Alotaibi,; Tareq Eid Saqer Al otaibi,; Zahim Ajjab Zahim Alotaibi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The nursing practice environment plays a critical role in influencing both the quality of patient care and nurses' job satisfaction, retention, and well-being. A positive work environment, characterized by structural empowerment, is essential to prevent nurse burnout and improve patient outcomes. This study examines the relationship between nurses' perceptions of their work environment, as measured by the Practice Environment Scale of the Nursing Work Index (PES-NWI), and their psychological empowerment, as assessed by the Psychological Empowerment Instrument (PEI). Understanding this relationship is crucial for improving both nurse performance and patient care. Methods: A secondary analysis was conducted using cross-sectional data from a two-year survey of 7,849 nurses . The PES-NWI, a validated tool to assess the work environment, and the PEI, a scale measuring psychological empowerment, were used. Descriptive statistics, Cronbach’s alpha, Pearson’s correlation, and multilevel analysis (hierarchical linear models) were employed to explore the relationship between the PES-NWI scores and PEI scores, controlling for demographic factors such as age, sex, educational background, and years of experience. Results: A total of 2,438 valid responses (31.1% valid response rate) were analyzed. The results revealed a significant positive relationship between the overall PES-NWI score and the PEI total score (r = 0.16–0.25, p < 0.001). Multilevel analysis confirmed that a supportive work environment, as indicated by higher PES-NWI scores, was positively associated with greater psychological empowerment (coefficient range: 0.33–0.72, p < 0.001). Conclusion: The findings indicate that a positive nursing practice environment, characterized by structural empowerment, is a key factor in enhancing psychological empowerment among nurses. This relationship underscores the importance of fostering a supportive work environment to improve nurse job satisfaction, retention, and ultimately, patient outcomes. Nursing managers should prioritize strategies that strengthen the work environment to empower nurses and enhance their engagement and effectiveness in clinical settings.